Ocular tuberculosis I: Epidemiology, pathogenesis and clinical features [Oküler tüberküloz I: Epidemiyoloji, patogenez ve klinik özellikler] - (:unkn) unknown (My University, 2011)
The World Health Organization has declared tuberculosis (TB) to be a global emergency, as it remains the most common single cause of morbidity and mortality worldwide. TB is caused by the acid-fast bacillus Mycobacterium tuberculosis and primarily affects the lungs [pulmonary TB (PTB)]. It can also affect any other part of the body [extrapulmonary TB (EPTB)]. It is estimated that 1.4% of patients with PTB will eventually develop ocular disease; however, in the majority of cases of ocular TB, PTB may not be documented. Ocular TB infection is usually a result of hematogenous spread during PTB or EPTB. Symptomatic disease most commonly develops after reactivation of dormant foci in the ocular tissue rather than being the manifestation of the initial infection. Immune-mediated ocular TB can occur due to hypersensitivity to M. tuberculosis antigens from a distant focus (such as lungs), despite the absence of the bacterium in the eye. The most common clinical presentation of intraocular inflammation (uveitis) due to TB appears to be posterior uveitis, followed by anterior uveitis, panuveitis and intermediate uveitis. The absence of uniform diagnostic criteria for intraocular TB has led to confusion regarding its diagnosis and management. Recent studies on the clinical importance of purified protein derivative (PPD) skin test, interferon-gamma release assays, chest computed tomography and polymerase chain reaction have provided a new approach to diagnosing ocular TB. This review series focuses on the clinical features, diagnostic techniques, diagnostic criteria, and treatment modalities in the light of recent literature.
Keywords: Diagnosis; Ocular involvement; Treatment; Tuberculosis; Uveitis